Evaluating the water quality of a Kondakarla Ava Lake for agricultural endeavours in Visakhapatnam, India - SIRISHA KORRAI; Vinay Sagar B; Madhavi Earle; Sangeetha Sankhyayani Achanta; Hemanshu Mediboyana (Zaštita Materijala)
Global population growth is placing a pressure on freshwater resources. Freshwater resources are becoming scarcer in terms of both quantity and quality due to the rising demand. Assessing water quality of surface water bodies for irrigation is essential as water with poor quality can pose health risks. The study involved observing the physicochemical parameters of Kondakarla Ava Lake from six different sampling locations. The study revealed that it could not use directly for drinking purposes as per NSFWQI. According to parameters like RSC, SAR, PI, % Na, and IWQI, water quality is appropriate for irrigation. It is further strengthened by the USSL diagram showing that the Kondakarla Ava Lake samples fall under the categories C3S1 and C4S1, which indicates that water has low sodium peril and high to very high salinity. The Wilcox diagram showed the grouping of the samples under three categories: excellent, good to permissible, and doubtful.